Clinicopathological and therapeutic features of metaplastic carcinoma of the breast: a study of 15 cases - Salhi, Hasna; Jaidane, Olfa; El Amine, Olfa; Ayadi, Med Malek; Hassouna, Jamel Ben; Dhieb, Tarek Ben; Hechiche, Monia; Amor, Gammoudi; Rahal, Khaled (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Metaplastic carcinoma of the breast is a rare entity containing a mixture of malignant epithelial and mesenchymal elements. The World Health Organization only recognized it as a distinct pathological entity since 2000. The aim of this study is to better characterize this rare disease. Methods: We reviewed retrospectively 15 cases of metaplastic carcinoma of the breast treated in our institute between 1994 and 2015. We analyzed clinical, histological, therapeutic and evolutive data. Results: All patients were females ranging from 29 to 75 years old (median, 50). Tumor size ranged from 20 to 150 mm (median, 72 mm). The Treatment consisted of radical mastectomy in 14 cases, often combined with post-operative radiation and/or chemotherapy. There were 8 cases of carcinosarcoma, 4 cases of spindle cell carcinoma and 3 cases of squamous cell carcinoma. Follow-up data were available on 12 patients. The median follow-up was 47 months (range, 10 to 146 months). Definitive nodal metastases were identified in 6 cases. One patient developed a local recurrence. Extranodal metastases occurred in 3 patients. Three patients died at median interval of 20 months (range, 13-30). Eight patients were alive with no evidence of recurrent or metastatic disease (median, 47 months) and one patient was alive with metastatic disease. Conclusions: Based on this series, metaplastic breast carcinoma is characterized by a large tumor size at presentation, a low frequency of nodal metastases and a high proportion of triple negativity. Our series is consistent with the literature.